Semiotic Analysis of Kabanti Tula-Tulana Koburu - Utari Azim, Nur Santriani; Sulistyowati, Sulistyowati; Winarti, Daru (Pioneer: Journal of Language and Literature, 2024)
This research aims to provide an interpretation regarding the aspects of life contained in the meaning of Kabanti Tula-Tulana Koburu in the Wolio community using semiotic analysis. This study used descriptive qualitative method. The data in this research is Kabanti Tula-Tulana Koburu which comes from the book Kabanti Oni Wolio (Wolio Language Poetry) Volume 1. To achieve the objectives of this research, a content analysis method was used using Charles Sanders Pierce's semiotic theory. This research is a literature study research. The results of the research conducted found that Kabanti Tula-Tulana Koburu invites us to reflect on various aspects of life such as death, limitations, challenges, hopes and the meaning of life. Kabanti Tula-tulana Koburu highlights the mortal and fragile nature of humans and the importance of facing destiny with awareness and thorough preparation. Apart from that, Kabanti also reminds us to stop negative behavior such as arrogance, excessive joy, and haram actions.